Detailed cultural heritage recording produced with traditional methods and laser scanning - Lah, Ljubo (Geodetski vestnik, 2023)
Traditional measurement methods are still widely used for recording cultural heritage objects. On the other hand, geodetic surveying and modern technologies such as 3D laser scanning can provide more accurate, geometrically consistent and extremely detailed data that can be used as a basis for detailed vector maps or 3D models. The main aim of our research was to investigate the complementary approach, using both traditional and modern methods, in order to produce detailed vector maps of the Romanesque church of St. Martin in Chapaize, France, which are essential for further unveiling its historic development. Geometrically, this church is rather extensive and has many irregularities in its shape. Our approach to the documentation process is presented and evaluated in this paper. We applied the Procrustes analysis for the ground floor map, which gave us an objective accuracy assessment. Point clouds of the bell tower acquired by two different laser instruments have also been compared.
Keywords: cerkve; Church of St. Martin in Chapaize; cultural heritage recording; geodezija; historical development; kulturna dediščina; laser scanning; lasersko skeniranje; Procrustes analysis; traditional measuring method